British Gynaecological Cancer Society recommendations for women with gynecological cancer who received non-standard care during the COVID-19 pandemic. Issue 1 (18th November 2021) - Taylor, Alexandra; Sundar, Sudha S; Bowen, Rebecca; Clayton, Rick; Coleridge, Sarah; Fotopoulou, Christina; Ghaem-Maghami, Sadaf; Ledermann, Jonathan; Manchanda, Ranjit; Maxwell, Hilary; Michael, Agnieszka; Miles, Tracie; et al.
Abstract : During the COVID-19 pandemic, pressures on clinical services required adaptation to how care was prioritised and delivered for women with gynecological cancer. This document discusses potential 'salvage' measures when treatment has deviated from the usual standard of care. The British Gynaecological Cancer Society convened a multidisciplinary working group to develop recommendations for the onward management and follow-up of women with gynecological cancer who have been impacted by a change in treatment during the pandemic. These recommendations are presented for each tumor type and for healthcare systems, and the impact on gynecological services are discussed. It will be important that patient concerns about the impact of COVID-19 on their cancer pathway are acknowledged and addressed for their ongoing care.